Rethinking tracking: Lessons from Hungary for German education reform - Sarah McNamara; Thilo Klein (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2025)
Educational tracking - separating students into different classes, tracks, or schools based on ability - is relatively commonplace worldwide, despite mixed evidence concerning how it affects student outcomes. Our new empirical analysis for secondary-school- aged children in Hungary provides causal evidence that students benefit from high-track attendance in terms of academic achievement and university aspirations. However, differential accession to the highest track conditional on socioeconomic background may exacerbate educational inequalities. Students from more deprived backgrounds are less likely to access the highest track, though we find they benefit at least as much from high-track attendance as their relatively better-off peers. Similarly, students with lower levels of prior achievement equally benefit from high-track attendance in terms of learning gains, and we find only minor evidence of academic peer spillovers. Overly restrictive tracking policies may therefore unnecessarily threaten educational equality goals, and in the German context, where tracking has been a cornerstone of the education system since the 19th century, particularly rigid and early tracking policies may further amplify these effects. Rethinking Germany's approach to tracking means re-centring discussions of equality in light of this new evidence for the efficiency-equity trade-off.
Keywords: 330